Detailed total ionizing dose effects on LDMOS transistors. (September 2022) - Houadef, Ali; Djezzar, Boualem
Abstract: The degradation of lateral double-diffused MOSFETs (LDMOS) due to total ionizing dose (TID) effects is examined in this paper using physics-based 2D TCAD simulations. The devices under test (DUTs) are built with a single reduced surface field (single-RESURF) structure and local oxidation of silicon (LOCOS) field oxide. The device structure was chosen for its topological simplicity in comparison to other modern LDMOS transistors to explore the impact of gamma radiation on small-AC and RF behavior. The results demonstrate fundamental differences between n-type (nLDMOS) and the p-type (pLDMOS) parameter shifts. Due to the distinct damage location in the pLDMOS, which is mainly the drift region, TID augments the values of the various parasitic capacitances. However, in the nLDMOS, TID reduced those values, especially the gate capacitance overshoot, as the degradation happens in the channel region and the bird's beak mostly. Consequently, the RF response and stability of the devices will differ. In addition, we present new research opportunities for TID effects on LDMOS transistors in particular, but also for radiation studies in general. Highlights: TCAD process simulation is conducted to get an accurate LDMOS transistor. Mesh discretization of the final device to account for the various oxide thicknesses and doping regions. Analytical calculation of the accumulated interface and bulk traps after radiation under a certain electric field. Checking the accuracy of the simulation setup by extracting the threshold voltage shift. Simulation of small-AC and RF behavior to see how TID affects various parasitic electric components.